THE ROLE OF HUMOUR IN TEACHING ORAL SPEECH (EDUCATION IN THE 21ST CENTURY, 2023)
It is of utmost importance for English teachers to help students to enhance speakingabilities. Humour has always been seen as enhancement to classroom teaching andlearning. Over time, the problem of humour caught the attention of many thinkers. Inlanguage teaching, a teacher can easily see that the learners are often motivated greatlywhen humour is used in classroom. Teachers' effective use of humor is generally viewedas a positive factor in the classroom and it is often identified as a teaching technique fordeveloping a positive learning environment. In the present article the role of humour isshown in promoting speaking through some elements of humour.
Keywords: humour, foreign language teaching, puns, puzzles and jokes, increasing motivation, teaching technique.